Digital Communication Competence of Foster Children: An Evaluation of the Four Pillars of Media Literacy at LKSA Kasih Ibu Bengkulu - Poppi Damayanti; M.Ridho Syabibi; Syabithah Iffah Jauharah Rudis (Yayasan Darussalam Bengkulu, 2026)
This study aims to evaluate the digital communication competence of foster children at the Child Social Welfare Institution (LKSA) Kasih Ibu, Bengkulu City, through the framework of the Four Pillars of Digital Literacy. Amid the rapid expansion of digital transformation, foster children living in alternative care institutions face unique challenges related to media supervision and communication risks within cyberspace. Methods: This study employed a quantitative descriptive statistical design using a census technique involving the entire population of foster children (N = 17). Data were collected through a structured questionnaire developed based on the Indonesian National Digital Literacy Framework established by the Ministry of Communication and Information Technology (Kominfo). The data were analyzed using percentage-based descriptive techniques. Results: The findings revealed an asymmetrical pattern of digital communication competence. Most respondents were adolescents aged 12–15 years and were enrolled in junior secondary education (53.30%). Specifically, the dimensions of Digital Ethics (54%) and Digital Skills (46.15%) were categorized as high, indicating polite communication behaviour and adequate technical proficiency in Computer-Mediated Communication (CMC). In contrast, Digital Safety was classified as low (46.15%), while Digital Culture was categorized as moderate (34.46%). Conclusion: The results indicate a gap between ethical communication practices and awareness of digital privacy protection. Although foster children demonstrate prosocial communication behaviours, they remain highly vulnerable to cybersecurity risks due to inadequate privacy management practices. This study recommends the implementation of caregiving policies and educational interventions focused on digital risk mitigation to protect marginalized children from potential threats and exploitation in digital public spaces.